Method for in-situ coating of positive electrode material with carbon-graphite and modified positive electrode material
By coating carbon-graphite in situ on the surface of the positive electrode material, and using the instantaneous high-temperature reaction in the piston flow reactor, the problems of insufficient connection between carbon and material and insufficient carbon graphitization in traditional processes are solved, and the improvement of lithium ion migration rate and optimization of material performance are achieved.
Patent Information
- Application Number
- CN202111162871.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-09-30
AI Technical Summary
In the traditional carbon coating process, carbon and material are only mixed during the stirring process, and a strong connection cannot be formed, and the sintering temperature is not enough to achieve carbon graphitization, resulting in limited increase in the migration rate of lithium ion.
The method of in-situ coating of carbon-graphite for the positive electrode material is adopted to coat carbon-graphite in-situ surface on the surface of the positive electrode material through instantaneous high-temperature reaction in the piston flow reactor, and efficient carbon-graphitization is achieved through atomization of organic solvents and oxidation reaction of nanopowders.
It realizes efficient migration of lithium ions, significantly improves the rate performance and cycle stability of the material, and improves storage resistance.
Smart Images

Figure CN114314579B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a method for in-situ coating of carbon-graphite on a positive electrode material and a modified positive electrode material. Background Art
[0002] In traditional technologies, improving battery rate performance is achieved by doping ternary electrode materials with elements, coating the surface, reducing the particle size of the material, etc. For example, element doping increases the migration rate of lithium ions, surface coating changes the interface impedance, and reducing the particle size of the material shortens the migration distance of lithium ions, thereby improving the rate performance of the material.
[0003] Among them, carbon coating of ternary electrode materials is one of the main means to improve cycle stability, rate capability, and capacity. However, the current process of most carbon coating processes is: in the battery positive electrode slurry step, a certain amount of conductive carbon black, carbon nanotubes, graphene and other substances are added to make a mixed slurry, which is then dried and sintered. The problems with this process are:
[0004] 1. It is only mixed with the material during the stirring process, and does not form a strong connection with the surface of the material, so the rate increase during the circulation process is limited;
[0005] Second, the sintering temperature range of ternary electrode materials is 700-900℃, which is far lower than the carbon graphitization temperature of 3000℃. Therefore, in the traditional process, carbon is not graphitized and cannot effectively improve the migration rate of lithium ions. Summary of the invention
[0006] The purpose of the present invention is to provide a method for in-situ coating of carbon-graphite on a positive electrode material. The method utilizes an instantaneous high-temperature reaction to in-situ coat the carbon-graphite on the surface of the positive electrode material, and the coating layer has a strong and stable bond with the positive electrode material, which can effectively increase the migration rate of lithium ions and efficiently improve the rate capability during the cycle process.
[0007] Another object of the present invention is to provide a modified positive electrode material, which has higher electrochemical properties such as rate performance and cycle performance than existing products, and also has better storage resistance.
[0008] In order to achieve the above objectives, the present invention provides the following technical solutions:
[0009] A method for in-situ coating of a positive electrode material with carbon-graphite, comprising:
[0010] Adding cathode material, organic solvent and nano powder into the plug flow reactor in sequence, and introducing oxygen therein; then pushing the piston rod of the plug flow reactor to compress until the organic solvent undergoes a decomposition chemical reaction, and the gas generated in the decomposition chemical reaction process pushes the piston rod out, and the reaction ends;
[0011] The organic solvent is added into the plug flow reactor in an atomized manner, the nano powder is sprayed into the plug flow reactor through an air flow, and the nano powder is a nano powder capable of undergoing an exothermic oxidation reaction.
[0012] The above method of the present invention mainly utilizes the high-temperature instantaneous reaction of an organic solvent. The reaction is carried out in situ on the surface of the positive electrode material, and the reaction generates carbon, most of which is then graphitized and coated on the surface of the positive electrode material. The specific reaction principle is as follows.
[0013] After adding the positive electrode material to the piston flow reactor, the organic solvent is sprayed into the reactor by atomization, so as to avoid the liquid causing the positive electrode material to agglomerate, and at the same time the atomized organic solvent is evenly distributed in the space; then the nano powder is brought into the piston reactor by the air flow, and forms evenly distributed fine (close to nanometer scale) suspended droplets with the organic solvent in the reactor; at this time, the piston rod is pushed to compress the space, and the mechanical energy is converted into thermal energy (the piston rod does work to compress the gas, which can increase the internal energy of the gas instantly. After the internal energy of the gas increases, the temperature in the cylinder is driven to rise and the reaction begins). Under the action of thermal energy, the nano powder acts as an ignition point to undergo an oxidation reaction in an oxygen atmosphere and releases a large amount of heat, generating a high temperature environment sufficient to decompose the organic solvent. The organic solvent decomposes on the surface of the ternary positive electrode material to form carbon, and the carbon further crystallizes to form graphite, accompanied by the generation of a large amount of gas (mainly carbon dioxide), which causes the pressure in the piston to increase and push the piston rod in reverse. When the piston rod is separated from the piston, the material in the reactor instantly contacts the air, completes cooling, and finally forms a carbon-graphite mixed coating layer. Before pushing the piston rod for compression, mixing can be enhanced, such as by shaking the reactor, so that the materials are mixed evenly.
[0014] The following technical effects were achieved in the above process:
[0015] (1) Atomization effect of organic solvent: Since the organic solvent is added to the container in the form of atomization, it has higher dispersibility, so a higher temperature can be obtained, the reaction is more complete, and the conversion rate of graphite is higher. The distribution on the surface of the positive electrode material is also more uniform, and the obtained coating layer can be thinner, thereby reducing the adverse effects of polarization and reducing the capacity of the coating material;
[0016] (2) Instantaneous high temperature effect of nanopowder: Since nanopowder acts as the ignition point, its extremely high specific surface area contains extremely high surface energy. When the oxygen concentration is relatively low and the temperature reaches a certain value, it will produce a redox reaction with oxygen to release a large amount of heat, thereby initiating a reaction, thereby reducing the initial pressure of the reactor, and being able to carry out the decomposition reaction of the organic solvent at a lower pressure, and also increasing the reaction rate in the reactor, so that high temperature can be generated instantly, so that the organic solvent can be decomposed instantly at high temperature. Such a short reaction time greatly avoids the performance degradation of the positive electrode material due to the high temperature reducing atmosphere of carbon; at the same time, it reduces the requirements for experimental production equipment, which can reduce production costs and increase process controllability;
[0017] (3) Rapid reaction: Nanopowders and organic solvents are added to the reactor in a highly dispersed form, so that the ignition point and the carbon source are evenly distributed, and the contact area between the two in the reactor is also larger, the heat exchange is faster, which is conducive to rapid reaction, and the organic solvent is decomposed within milliseconds;
[0018] (4) In-situ coating: The method of mixing carbon sources in the pulping stage of the prior art belongs to physical coating, while the present invention adopts in-situ chemical coating. Compared with other simple physical coatings, in-situ coating has strong bonding force and can avoid falling off. Moreover, since carbon and graphite are coated in-situ, the positive electrode material and the coating layer are combined at the chemical level (with strong bonding in crystal size), and no transition is required during the migration of lithium ions (taking lithium batteries as an example, the principles of other batteries are similar), and they can be quickly released and embedded along the migration path of positive electrode material-coating layer-electrolyte. In addition, carbon and graphite are coated in-situ to achieve uniform surface coating, and the surface of the coating layer is smoother, thereby improving the wettability of the material surface with the electrolyte, increasing the active area of the electrolyte contact reaction, and effectively improving the rate performance.
[0019] (5) Graphitization of carbon: Due to the high temperature, the conversion rate of carbon to graphite can be increased. Therefore, the surface of the coating layer is composed of a composite of carbon and graphite. The unique crystal structure of graphite can form a good solid electrolyte (SEI) film on the surface of the material, reducing the lithium ion migration impedance and achieving the result of improving the rate performance;
[0020] (6) Fast cooling rate: The final cooling is completed by the instantaneous contact between the material and the external environment after the piston is pushed out. That is, when the critical pressure in the reactor is exceeded, the pressure can be released instantly so that the material can be cooled quickly. The entire reaction is completed in the instant of piston compression, which has extremely high production efficiency.
[0021] In the present invention, the positive electrode material mainly refers to materials suitable for carbon and graphite coating; carbon and graphite act as reducing agents, increasing the conductivity of electrons between particles and on the surface; they also inhibit the growth of positive electrode material grains and increase the specific surface area; they also act as nucleating agents to reduce the particle size of the product; and they also adsorb and maintain the stability of the electrolyte.
[0022] In some preferred embodiments, the positive electrode material is a ternary positive electrode material for a lithium battery, including but not limited to typical lithium nickel cobalt manganese metal composite oxides and the like.
[0023] In some preferred embodiments, the positive electrode material is properly treated before being added to the reactor to ensure that the water content is below 200 ppm, more preferably below 100 ppm.
[0024] This is because if the water content of the positive electrode material is too high, the water evaporates and absorbs heat during the reaction, which may cause the temperature to fail to reach the critical point of carbon graphitization. The method for removing water is arbitrary, such as a simpler drying method. For common lithium battery ternary positive electrode materials, vacuum drying at 120-200℃ for a certain period of time can meet the requirements.
[0025] The key role of the organic solvent in the present invention is to provide a carbon source, so it is preferred that the type has a low decomposition temperature and is not easily introduced with impurities. On the other hand, the organic solvent should be liquid at room temperature, which is more conducive to coating the surface of the positive electrode material and efficient contact with the nanopowder.
[0026] In some preferred embodiments, the organic solvent is selected from C1-12 hydrocarbons.
[0027] In some preferred embodiments, the organic solvent comprises at least one of n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, toluene and xylene, more preferably n-hexane or n-decane.
[0028] The amount of the organic solvent added is related to the final required carbon coating amount. When the process of the present invention is used to coat carbon-graphite, the following amount is preferably used:
[0029] The amount of the organic solvent added is 1%-8% of the weight of the positive electrode material, and any ratio within this range can be selected, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc.
[0030] Under this condition, higher rate capability can be obtained with less adverse effects on other properties.
[0031] The main function of the nano powder in the present invention is ignition and heat release, so the nano powder oxidation reaction releases a large amount of heat, is easy to oxidize, and is not easy to introduce adverse impurities. The added amount is also controlled within a small amount range as much as possible.
[0032] In some preferred embodiments, the nano powder includes at least one of carbon, sulfur, metal, ferrous oxide, flour, starch, glucose, and milk powder, and the particle size should be nanometer scale.
[0033] In some preferred embodiments, the metal includes at least one of lithium, iron, sodium, magnesium, aluminum, and nickel.
[0034] In some preferred embodiments, the nano powder is a mixture of nano carbon powder and nano sulfur powder.
[0035] In some preferred embodiments, the nano powder is a mixture of nano carbon powder and nano sulfur powder, and the mass ratio of the nano carbon powder to the nano sulfur powder is 1:1.
[0036] In some preferred embodiments, the ratio of the amount of the nanopowder added to the volume of the plug flow reactor is (9.7-33.5) g:1 m 3 , which is equivalent to the ignition content or ignition coefficient, and can be any value within the optional range. For example, 9.7g, 10.0g, 11g, 13g, 15g, 17g, 20g, 22g, 25g, 26g, 27g, 28g, 28.5g, 29g, 30g, 30.5g, 31g, 32g, 32.5g, 33g, 33.5g, etc. of nano powder can be added into every cubic meter of reactor.
[0037] In the present invention, a catalyst may be added, and the catalyst may catalyze the high-temperature decomposition of the organic solvent or catalyze the graphitization of carbon.
[0038] In some preferred embodiments, the catalyst is ferrocene.
[0039] Ferrocene is a catalyst for improving the degree of graphitization. After adding ferrocene, it can reduce the graphitization temperature, improve graphitization, and catalyze the formation of fullerenes, carbon nanotubes and other substances to enhance the conductive properties.
[0040] Since ferrocene is a solid substance and is not easy to be highly dispersed, in order to improve its utilization rate, in some preferred embodiments, ferrocene is added in the following manner:
[0041] Before adding the organic solvent, ferrocene is dissolved in the organic solvent to form an organic solution, which is then added to the plug flow reactor in an atomized manner.
[0042] The amount of ferrocene added is closely related to the amount of the organic solvent. In order to achieve a better catalytic effect, the weight of the ferrocene is preferably 1% to 5% of the total weight of the organic solvent, for example 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0043] In some embodiments, the weight of the ferrocene is preferably 3% to 5% of the total weight of the organic solvent; in some embodiments, the weight of the ferrocene is preferably 5% of the total weight of the organic solvent.
[0044] In the present invention, the oxygen atmosphere in the plug flow reactor is to control the reaction temperature, reduce the reaction pressure, and the final carbon coating amount. Taking all these into consideration, the oxygen content in the plug flow reactor is preferably 20% to 40%, for example 20%, 25%, 30%, 35%, 40%, etc.
[0045] In the present invention, nano powders are sprayed into the reactor through an airflow, and the airflow can be any inert gas or any gas conducive to the reaction. Preferably, oxygen is sprayed into the reactor, or a mixture of oxygen and an inert gas, which simultaneously supplies the oxygen required for the reaction and improves production efficiency.
[0046] In addition, the means for realizing the atomization of the organic solvent of the present invention are arbitrary, including but not limited to existing dispersion technologies such as nozzles and high-speed airflow, and dispersion technologies with better effects in the future may also be used.
[0047] The modified positive electrode material prepared by any coating method described above in the present invention is suitable for various types of batteries, including typical lithium batteries.
[0048] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0049] (1) Achieve high-temperature instantaneous coating;
[0050] (2) Reduce the deterioration effect of carbon or graphite reducing atmosphere on the performance of positive electrode materials;
[0051] (3) Increased bonding strength between the coating layer and the positive electrode material;
[0052] (4) Instantaneous rapid cooling is achieved;
[0053] (5) The safety and rate performance of cathode materials are greatly improved;
[0054] (6) The graphite content in the coating layer is higher;
[0055] (7) The coating process is simplified. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0057] Figure 1 TEM image of the material obtained in Example 1 is shown;
[0058] Figure 2A Raman characterization comparison diagram of Example 1 and Comparative Example 1 is shown;
[0059] Figure 3 A comparison chart of the stability of the coating layer during Example 1 and mechanical coating is shown. DETAILED DESCRIPTION
[0060] The embodiments of the present invention will be described in detail below in conjunction with examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. The original drugs, reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be purchased commercially or can be prepared according to the prior art.
[0061] Example 1
[0062] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0063] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0064] 3. Weigh 5g of n-hexane organic solvent accounting for 5% of the mass ratio of the positive electrode material, and weigh 0.25g of ferrocene accounting for 5% of the mass ratio of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0065] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0066] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0067] Example 2
[0068] 1. Weigh 100g of LiNi0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0069] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0070] 3. Weigh 3g of n-decane organic solvent accounting for 3% of the mass ratio of the positive electrode material, and weigh 0.15g of ferrocene accounting for 5% of the mass ratio of the organic solvent. Add the weighed ferrocene into n-decane to dissolve into a mixed organic solution for standby use.
[0071] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0072] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0073] Example 3
[0074] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0075] 2. This experiment uses a 0.001 cubic meter reactor with the ignition coefficient set at 25. Weigh 0.025 g of flour and set aside.
[0076] 3. Weigh 5g of n-hexane organic solvent accounting for 5% of the mass ratio of the positive electrode material, and weigh 0.25g of ferrocene accounting for 5% of the mass ratio of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0077] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0078] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0079] Example 4
[0080] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0081] 2. This experiment uses a 0.001 cubic meter reactor, the ignition coefficient is set at 9.7, and 0.0097 g of nano-carbon powder is weighed for use.
[0082] 3. Weigh 5g of n-hexane organic solvent accounting for 5% of the mass ratio of the positive electrode material, and weigh 0.25g of ferrocene accounting for 5% of the mass ratio of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0083] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0084] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0085] Example 5
[0086] 1. Weigh 100g of LiNi 0.8Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0087] 2. This experiment uses a 0.001 cubic meter reactor, the ignition coefficient is set at 33.5, and 0.0335 g of nano-carbon powder is weighed for use.
[0088] 3. Weigh 5g of n-hexane organic solvent accounting for 5% of the mass ratio of the positive electrode material, and weigh 0.25g of ferrocene accounting for 5% of the mass ratio of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0089] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0090] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0091] Example 6
[0092] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0093] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0094] 3. Weigh 1g of n-hexane organic solvent with a mass ratio of 1% of the positive electrode material, and weigh 0.05g of ferrocene with a mass ratio of 5% of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0095] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0096] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0097] Example 7
[0098] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0099] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0100] 3. Weigh 8g of n-hexane organic solvent accounting for 8% of the mass ratio of the positive electrode material, and weigh 0.4g of ferrocene accounting for 5% of the mass ratio of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0101] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0102] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0103] Example 8
[0104] 1. Weigh 100g of LiNi0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0105] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0106] 3. Weigh 5g of n-hexane organic solvent with a mass ratio of 5% of the positive electrode material, and weigh 0.25g of ferrocene with a mass ratio of 5% of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0107] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the piston reactor cylinder by atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 40%.
[0108] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0109] Comparative Example 1
[0110] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0111] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0112] 3. Weigh 5 g of n-hexane organic solvent with a mass ratio of 5% of the positive electrode material and set aside. In this experiment, ferrocene is not added.
[0113] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic solvent in the third step into the piston reactor cylinder by atomization; then bring the nanopowder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to 22%.
[0114] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. At this time, when the piston rod is pushed to a certain position, the internal reaction materials begin to react and push the piston rod back out of the piston. The reaction ends after the piston rod is pushed out of the piston. After the reactants are cooled, they are collected. At this time, the collected materials are carbon / graphite in-situ coated ternary positive electrode materials.
[0115] Comparative Example 2
[0116] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0117] 2. This experiment used a 0.001 cubic meter reactor, and this comparative example was tested without adding nanopowder.
[0118] 3. Weigh 5g of n-hexane organic solvent with a mass ratio of 5% of the positive electrode material and set aside. Weigh 0.25g of ferrocene with a mass ratio of 5% of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution and set aside.
[0119] 4. Place the ternary cathode material weighed in the first step into the piston reactor; spray the organic mixed solution in the third step into the cylinder of the piston reactor by atomization; control and adjust the oxygen content in the piston reactor to control the oxygen content of the piston reactor at 22%.
[0120] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. When the piston is pushed to the same position as in Example 1, the reaction does not proceed, so stop the reaction.
[0121] Comparative Example 3
[0122] 1. Weigh 100g of LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, vacuum dried at 200℃ for 120min, and vacuum cooled for standby use.
[0123] 2. This experiment uses a 0.001 cubic meter reactor with an ignition coefficient set at 20. Weigh 0.01g of nano-carbon powder and 0.01g of nano-sulfur powder and mix them evenly for later use.
[0124] 3. Weigh 5g of n-hexane organic solvent with a mass ratio of 5% of the positive electrode material, and weigh 0.25g of ferrocene with a mass ratio of 5% of the organic solvent. Add the weighed ferrocene into n-hexane to dissolve into a mixed organic solution for standby use.
[0125] 4. Place the ternary cathode material weighed in the first step into the piston reactor; place the organic mixed solution in the third step directly into the piston reactor cylinder without atomization; then bring the nano powder weighed in the second step into the piston reactor cylinder through oxygen. Control and adjust the oxygen content in the piston reactor to keep the oxygen content of the piston reactor at 22%.
[0126] 5. After the above preparations are completed, shake the piston reactor to mix the internal materials thoroughly. Then push the piston rod to compress the materials in the cylinder. When the piston is pushed to the same position as in Example 1, the reaction does not proceed, so stop the reaction.
[0127] Test data
[0128] 1. Observe the reaction conditions in the reactor, test the carbon content and graphitization degree in the coating layer of the obtained material, and test the 1C / 0.1C ratio. The results are shown in Table 1.
[0129] Among them, the specific test method of 1C / 0.1C rate is:
[0130] The positive electrode sheet is composed of active material, acetylene black and PVDF (mass ratio is 9:0.5:0.5). The cathode slurry is 3-4 mg / cm 2 The density of the material was coated on the collector Al foil. CR2025 coin-type batteries were assembled in an Ar atmosphere glove box, using lithium metal as the negative electrode, the electrolyte was 1M LiPF6 solution, and the solvent was a mixed solution of DMC:EMC:EC (volume ratio of 1:1:1). The electrochemical performance of the material was studied using a Xinwei battery test system at different rates (1C = 180mAh / g).
[0131] After the first discharge capacity is obtained at a rate of 0.1C, the second discharge capacity is obtained by testing at a rate of 1C for 5 minutes. The second discharge capacity / first discharge capacity = 1C / 0.1C.
[0132] Carbon content refers to: the mass content of carbon element in the final positive electrode material.
[0133] I D / I GRefers to: the ratio of the D peak and the G peak in the Raman spectrum of carbon materials. The smaller the value, the higher the degree of graphitization.
[0134] Table 1
[0135] Carbon content (%) <![CDATA[I D / I G ]]> Reaction results 1C / 0.1C(%) Example 1 1.22 0.87 normal 97.43 Example 2 1.54 0.82 normal 97.71 Example 3 1.23 0.85 normal 97.26 Example 4 1.69 0.91 normal 96.61 Example 5 1.57 0.90 normal 96.74 Example 6 0.33 0.80 normal 95.80 Example 7 1.77 0.93 normal 96.33 Example 8 0.89 0.87 normal 95.56 Comparative Example 1 1.30 1.11 normal 90.58 Comparative Example 2 3.55 / Not conducted 72.14 Comparative Example 3 3.76 / Not conducted 66.91
[0136] Among them, Example 1 and Example 2 replaced different organic solutions, and the carbon content test results showed that the carbon content of Example 2 was higher than that of Example 1. This was mainly because the organic solvent used had a relatively long carbon chain and required a higher temperature and time to decompose completely, so the mass of the added carbon source was relatively small, and the carbon coating amount was still high.
[0137] In Example 1 and Example 3, the ignition material is replaced by flour from a combination of carbon powder and sulfur powder, and corresponding adjustments are made to the content, but products with very similar effects can be prepared, which shows that within the conditions of the present technical solution, materials with excellent properties can be prepared.
[0138] The main difference between Example 1 and Example 4 and Example 5 is that the ignition coefficient of Example 1 is an intermediate value of 20, the ignition coefficient of Example 4 is a low value of 9.7, and the ignition coefficient of Example 5 is a high value of 33.5. The experimental results show that the carbon content of Examples 4 and 5 is higher than that of Example 1. Because of the lowest ignition coefficient in Example 4, the temperature in the piston flow reactor is relatively low, and part of the carbon source is not converted into carbon monoxide and carbon dioxide to escape. In Example 5, because of the highest ignition coefficient, the reaction speed is faster, and the rapid expansion of the gas causes the piston to quickly push out of the piston flow reactor, causing internal cooling, and part of the carbon source is not converted into carbon monoxide and carbon dioxide to escape. Therefore, the carbon content of Examples 4 and 5 is higher than that of Example 1, but the performance of the three is relatively close, which shows that within the conditions of the present technical solution, materials with excellent properties can be prepared.
[0139] The main difference between Example 1 and Example 6 and Example 7 is that the amount of organic solvent added in Example 1 is 5% as an intermediate value, the amount of organic solvent added in Example 6 is 1% as a low value, and the amount of organic solvent added in Example 7 is 8% as a high value. The lower amount of organic solvent added in Example 6 results in a lower final carbon content, which may result in incomplete coating, and the rate performance of Example 1 is better than that of Example 6, while the higher amount of organic solvent added in Example 7 results in a higher final carbon content, which may result in an overly thick coating layer, and the rate performance of Example 1 is better than that of Example 7. However, the performances of the three are relatively close, which shows that within the conditions of the present technical solution, materials with excellent properties can all be prepared.
[0140] The main difference between Example 1 and Example 8 is the oxygen flow rate. The experimental results show that the carbon content of Example 8 is lower than that of Example 1. As the oxygen content in the piston flow reactor increases, the oxidation reaction of the organic solvent is intensified, causing more organic solvent to be converted into carbon monoxide and carbon dioxide to escape, thereby reducing the carbon content.
[0141] The main difference between Example 1 and Comparative Example 1 is that ferrocene is not added in Comparative Example 1. The results show that the degree of graphitization is lower than that of Example 1, and the improved rate performance of the material is inferior to that of Example 1. Figure 2 The Raman spectra of Example 1 and Comparative Example 1 after characterization are shown. It can be clearly seen from the figure that the degree of graphitization of Example 1 is better than that of Comparative Example 1.
[0142] The main difference between Example 1 and Comparative Example 2 is that no nano powder is added in Comparative Example 2, resulting in the reaction failing to proceed normally. The main reason is that when there is no nano powder in the system, the compression work done by pushing the piston cannot generate high temperature in the internal material and continue to promote the reaction, so the reaction fails.
[0143] The main difference between Example 1 and Comparative Example 3 is the way of adding the organic solvent. Example 1 is atomized, and Comparative Example 3 is directly added as a liquid. Example 1 directly reacts normally by atomization, while Comparative Example 3 directly adds the liquid, which makes all the positive electrode materials wet and agglomerate together. In addition, since the piston flow reactor is not filled with organic solvent, the reaction does not proceed normally.
[0144] 2. TEM image of the material in Example 1 Figure 1 As shown, the surface of the material is coated with a layer of nano-scale carbon, the thinnest of which is less than 5 nm, indicating that the process of the present invention can achieve a thinner coating layer.
[0145] 3. Observe the bonding between the coating and the material
[0146] Example 1 and mechanically coated graphite (mechanical coating refers to adding ternary positive electrode materials and graphite into a high-speed mixer for mechanical coating) The coating strength of the coating layer is as follows Figure 3 As shown, after 60 minutes of magnetic stirring at 400 rpm / min and standing for 12 hours, it can be clearly seen from the figure that a large amount of graphite exists on the water surface after mechanical coating, indicating that a large amount of graphite has detached, while only a small amount of graphite exists on the water surface in Example 1, indicating that the coating effect of this technical solution is better than that of mechanical coating.
[0147] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for in-situ coating of positive electrode materials with carbon-graphite, characterized in that: include: Adding cathode material, organic solvent and nano powder into the plug flow reactor in sequence, and introducing oxygen into the reactor; Then, the piston rod of the plug flow reactor is pushed to compress until the organic solvent undergoes a decomposition chemical reaction, and the gas generated during the decomposition chemical reaction pushes the piston rod out, and the reaction ends; The organic solvent is added into the plug flow reactor in an atomized manner, the nano powder is sprayed into the plug flow reactor through an air flow, and the nano powder is a nano powder capable of undergoing an exothermic oxidation reaction, and the nano powder includes at least one of carbon, sulfur, and flour.
2. The method according to claim 1, characterized in that The ratio of the amount of the nano powder added to the volume of the plug flow reactor is (9.7-33.5) g:1 m 3 .
3. The method according to claim 1, characterized in that The organic solvent is selected from C1-12 hydrocarbons.
4. The method according to claim 3, characterized in that The organic solvent comprises at least one of n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, toluene and xylene.
5. The method according to claim 4, characterized in that The organic solvent is selected from n-hexane or n-decane.
6. The method according to claim 3, characterized in that The amount of the organic solvent added is 1%-8% of the weight of the positive electrode material.
7. The method according to claim 1, characterized in that The positive electrode material is a ternary positive electrode material for a lithium battery.
8. The method according to claim 7, characterized in that The water content of the positive electrode material is below 200 ppm.
9. The method according to claim 1, characterized in that: Before adding the organic solvent, ferrocene is dissolved in the organic solvent to form an organic solution, which is then added to the plug flow reactor in an atomized manner.
10. The method according to claim 9, characterized in that The weight of the ferrocene is 1% to 5% of the total weight of the organic solvent.
11. The method according to any one of claims 1 to 10, characterized in that: The oxygen content in the plug flow reactor is 20-40%.
12. The method according to claim 11, characterized in that The nano powder is sprayed into the plug flow reactor by oxygen or a mixed gas of oxygen and an inert gas.
13. A modified positive electrode material, characterized in that: It is prepared by the method described in any one of claims 1 to 12.
14. A lithium battery, characterized in that: Contains the modified positive electrode material according to claim 13.
Citation Information
Patent Citations
Preparation method of carbon-encapsulated high-nickel ternary cathode material
CN109390576A
Method for preparing metal oxide film-coated lithium ion positive electrode material
CN110620219A